2014
DOI: 10.5604/1232-1966.1108607
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function, physical activity and body composition in adult rural population

Abstract: The values of functional parameters of the respiratory system were suitable for the age they were within the norm and did not show lung ventilation disorder. Most subjects of the study declared low physical activity which may be due to manual work on the farm. Smoking cigarettes significantly lowered the value of such parameters as FEV1, PEF and MEF50 only in the male group but the values did not indicate ventilatory disorder. Parameters of the respiratory system show the highest correlations with the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…Quehenberger et al [40] and Kim et al [41] found positive correlations between perceived health condition and the level of PA. This can be justified by the proven positive impact of physical exercise of an appropriate duration, frequency, and intensity on health condition in adults [42,43]. Perceived health condition, however, does not only depend on one's objective health status, but is also determined by psychological and cultural factors, such as one's lifestyle or socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Quehenberger et al [40] and Kim et al [41] found positive correlations between perceived health condition and the level of PA. This can be justified by the proven positive impact of physical exercise of an appropriate duration, frequency, and intensity on health condition in adults [42,43]. Perceived health condition, however, does not only depend on one's objective health status, but is also determined by psychological and cultural factors, such as one's lifestyle or socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aerobic exercise and resistance exercise are effective ways of improving lung function. Besides, recent studies have shown that muscle strength and respiratory function are correlated 36 ) . Hand-grip strength also affects the pulmonary function of healthy older adults 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the significant role of physical activity in the prevention and treatment of diseases that often lead to premature death [1,2,3]. Positive correlations between physical activity and physical performance and fitness have also been proven [4]. Undertaking physical activity of the proper frequency, volume, and intensity has beneficial effects on both the mental health [5] and overall quality of life of adults [6,7,8].…”
Section: Introductionmentioning
confidence: 89%